Effects of chamber oxygen concentration on microstructure and mechanical properties of stainless steel 316L parts by selective laser melting - Sun, Zhongji (2018)
Selective laser melting (SLM) is a disruptive additive manufacturing technology that makes metal parts directly from 3D models in an automate layer-wise manner. Numerous studies have been carried out to examine the effects of various factors, such as laser power, scanning parameter, powder feedstock shape, substrate temperatures etc, on the microstructure and mechanical properties of SLM-built parts. The present work focused on the influence of chamber oxygen concentration towards the SLM-built stainless steel 316L (SS316L) parts. Chamber oxygeninduced amorphous silicon-enriched nano-particles have been found to be ubiquitous in SLM-built SS316L parts. However, the contribution of these nano-particles towards the built part’s mechanical properties is still unclear. Three batches of SS316L samples with varying chamber oxygen concentrations of 0.08 mol%, 0.16 mol% and 0.24 mol% were fabricated by SLM. Tensile and Vickers hardness tests were conducted. Backscatter Electron Microscopy was employed to elucidate the mechanisms of these amorphous nano-particles on the overall mechanical performance.